ANALYSIS OF THE QUALITY OF WEB-BASED ONLINE EXAMS IN THE EDUCATION AND TRAINING AGENCY OF THE INDONESIAN ATTORNEY GENERAL'S OFFICE USING ISO 25010 STANDARDS - Ardian Ramadita Muhram; Metty Mustikasari (Indonesian Journal of Multidisciplinary Science, 2022)
The Education and Training Agency for the Attorney General's Office of the Republic of Indonesia is one of the institutions that requires flexible and distributed learning. In the exam assessment process, the Education and Training Agency of the Attorney General's Office of the Republic of Indonesia collects data on questions given to participants in the form of files. The file is then used by participants to answer questions, then the answer file is sent to the organizers for inspection and assessment. With the implementation of such an exam, various problems arise which result in frequent delays in receiving the exam results report because the organizers experience time and energy constraints in manually correcting participants' answers one by one. Other problems that occur arise from the condition of the answer file which is often lost or deleted due to the error of the participants. Based on the above problems, the Education and Training Agency of the Indonesian Attorney General's Office feels the need to apply information technology. The creation of this web-based online exam system has been implemented since the beginning of 2022 until April 2022. The online exam system has been used in May and has started to be used. To find out whether the quality of the web-based online exam system has met the initial goal to be achieved, namely to facilitate the organizers in carrying out the exam process, assessing training participants' answers and making reports on the results of the assessment, a system evaluation is needed. This study aims to analyze the online exam system used in the Education and Training Agency of the Indonesian Attorney General's Office which is currently being used with the ISO 25010 method of product quality dimensions. The objectives to be achieved with this thesis research are to analyze the quality of the online exam system at the Indonesian Attorney's Education and Training Agency using the ISO 25010 standard, and to provide input and suggestions for improving the online exam system at the R.I Attorney's Education and Training Agency. Based on the results of research and discussions that have been carried out using the ISO 25010 standard method, the quality of the online examination system of the Indonesian Attorney's Education and Training Agency is quite feasible and meets the criteria.